Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1590/s0103-64402006000300001
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterization of the tooth/adhesive interface

Abstract: The purpose of this study was to assess the morphological characteristics of the tooth/adhesive interface using different adhesive systems in MOD restorations under scanning electron microscopy (SEM). The tested hypothesis was that the morphology of the bonding interface would vary in different areas of MOD restorations for the three adhesive systems. MOD cavities were prepared in 12 sound extracted human third molars and restored with Filtek Z250 composite resin and one of the following adhesive systems: Expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…The effectiveness of a self-etch adhesive system depends on multiple factors. The result of this study was in agreement with Moura et al, who demonstrated that self-etch systems showed lower bond strength compared to total-etch bonding agents (30) .Shinohara et al, concluded that low bond strength with questionable bonding effectiveness was achieved with self-etching adhesive systems (31) . Nakabayashi and Takarada noticed that the hydrophilic nature and evaporable solvent responsible for low bonding ability of the self-etching systems (32) .…”
Section: Discussionsupporting
confidence: 91%
“…The effectiveness of a self-etch adhesive system depends on multiple factors. The result of this study was in agreement with Moura et al, who demonstrated that self-etch systems showed lower bond strength compared to total-etch bonding agents (30) .Shinohara et al, concluded that low bond strength with questionable bonding effectiveness was achieved with self-etching adhesive systems (31) . Nakabayashi and Takarada noticed that the hydrophilic nature and evaporable solvent responsible for low bonding ability of the self-etching systems (32) .…”
Section: Discussionsupporting
confidence: 91%
“…Gaps/artifacts were observed in dentinal areas of adhesive/dentine interfaces, indicating that dentine bonding is likely to be influenced by more factors than enamel [49]. The observed gap in these areas may have originated from or may have been increased by air drying and desiccating the specimens for SEM observation.…”
Section: Discussionmentioning
confidence: 99%
“…The key characteristic of these systems is that they skip the acid etching stage prior to application 10 , greatly decreasing the level of technical sensitivity required 11 , particularly because they obviate the need for optimal dentin moisture, which is required for total-etch systems [12][13][14][15] . Unlike conventional adhesive systems, self-etch systems have added monomers added to their composition that ensure etching of the dental structure, so that, as soon as an area of the tooth is etched (or decalcified), it is immediately occupied by the resin monomer 7,16 . Due to the limited conditioning ability of self-etch adhesive systems, the hybrid layer they form is thinner 15,[17][18] as compared to that of conventional adhesive systems.…”
Section: Introductionmentioning
confidence: 99%